2020
DOI: 10.1007/s10453-020-09673-5
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 lockdown: a boon in boosting the air quality of major Indian Metropolitan Cities

Abstract: The COVID-19 lockdown has not only helped in combating the community transmission of SARS-CoV-2 but also improved air quality in a very emphatic manner in most of the countries. In India, the first phase of COVID-19 lockdown came into force on March 25, 2020, which was later continued in the next phases. The purpose of this study was to investigate the result of lockdown on air quality of major metropolitan cities—Delhi, Mumbai, Kolkata, Chennai, Bengaluru, Hyderabad, Jaipur, and Lucknow—from March 25 to May 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“… This Study Hyderabad 25 March to 3 May 2020 25 March to 03 May 2019 -23 -41 -37 -9 -29 Na The concentration of almost all pollutants have decreased ranging from -9 to -41 percent. Rathore et al, 2021 Kolkata 25 March to 30 April 2020 25 Feb. to 24 March 2020 -50 -51 -69 -40 12 Na PM 10 , PM 2.5 and NO 2 shows >50% decrease. O 3 was slightly increased during lockdown.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“… This Study Hyderabad 25 March to 3 May 2020 25 March to 03 May 2019 -23 -41 -37 -9 -29 Na The concentration of almost all pollutants have decreased ranging from -9 to -41 percent. Rathore et al, 2021 Kolkata 25 March to 30 April 2020 25 Feb. to 24 March 2020 -50 -51 -69 -40 12 Na PM 10 , PM 2.5 and NO 2 shows >50% decrease. O 3 was slightly increased during lockdown.…”
Section: Resultsmentioning
confidence: 98%
“…From Table 1 , it is found that the maximum decrease in NO 2 concentration was reported at Mumbai (-75%) followed by Kolkata (-69%) and the minimum decrease was reported at Singrauli (-12.5%). As NO 2 and NH 3 are primarily associated with the combustion of fuel like gasoline and diesel in vehicles and industries ( Mahato et al, 2020 ; Rathore et al, 2021 ). This maximum reduction in NO 2 and NH 3 could be attributed to the sudden shutdown of the transportation sector, except for emergency services, as transport is the major source of NO 2 emissions ( Hakim et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of them belongs to an industrial site. At SS-01 and SS-02, PM 10 and PM 2.5 were found above the limit and this may be due to dust arising from the foot of travelers and transport [ 30 ] in the area as two sites are marketing hubs of the city as mentioned in the material and method section. Values of PM 10 observed during the study period (82–235 µg/m 3 ) were found above the NAAQ value which is 100 µg/m 3 at all the sites.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is demonstrated that pollen allergies appear to be more prevalent in polluted areas, especially areas with heavy traffic (Lucas et al 2019). However, in 2020, the air quality substantially improved in numerous countries due to the COVID-19 lockdown accompanied by restricted movement of the public and shut down of industrial establishments (Dantas et al 2020;Rathore et al 2021). In Slovakia, the first phase of COVID-19 lockdown came into force on March 16, 2020, which later continued in the next phases.…”
Section: Introductionmentioning
confidence: 99%